2021
DOI: 10.1186/s40461-020-00106-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding why apprentices consider dropping out: longitudinal prediction of apprentices’ workplace interest and anxiety

Abstract: Although apprenticeships ease the school-to-work transition for youth, many apprentices seriously consider dropping out. While associated with noncompletions, dropout considerations are important to study in their own right, because they reflect a negative quality of apprenticeship experience and can impact apprentices’ quality of learning and engagement. Few studies have addressed apprentices’ dropout considerations using comprehensive theoretical frameworks. To address this gap, this study examined how appre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…In line with previous research, apprentices with high CSE might evaluate their situational resources more positively (Judge & Bono, 2001;Wu & Griffin, 2012), and they might be more confident asking for information, feedback, or more autonomy to achieve even better learning conditions (Judge & Kammeyer-Mueller, 2011;Mikkonen et al, 2017). Such learners shape their learning environments to improve their learning situation and make it more rewarding (Hirschi et al, 2015;Judge & Kammeyer-Mueller, 2011;Powers & Watt, 2021). Our finding that high levels of CSE are related to better resource profiles is also in line with COR theory (Hobfoll et al, 2018), which stipulates that having resources facilitates the further accumulation of resources.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In line with previous research, apprentices with high CSE might evaluate their situational resources more positively (Judge & Bono, 2001;Wu & Griffin, 2012), and they might be more confident asking for information, feedback, or more autonomy to achieve even better learning conditions (Judge & Kammeyer-Mueller, 2011;Mikkonen et al, 2017). Such learners shape their learning environments to improve their learning situation and make it more rewarding (Hirschi et al, 2015;Judge & Kammeyer-Mueller, 2011;Powers & Watt, 2021). Our finding that high levels of CSE are related to better resource profiles is also in line with COR theory (Hobfoll et al, 2018), which stipulates that having resources facilitates the further accumulation of resources.…”
Section: Discussionsupporting
confidence: 69%
“…Regarding learning in apprenticeships, scholars have highlighted that aspects such as high-quality instruction, guidance, and support and the opportunity to work on varied tasks in a self-determined manner play key roles in the development of vocational competencies and the formation of vocational identities (Mikkonen et al, 2017;Nisula & Metso, 2019). Apprentices with higher situational resources not only learn faster and better, they also evaluate their learning environments more positively, maintain interest and motivation, and cope better with challenges and demands that arise at work or school (Powers & Watt, 2021;Reegård, 2015).…”
Section: Situational Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…This physiological activation saps employees' mental and emotional resources, leading to a loss of energy and ultimately to health impairments (Bakker and Demerouti, 2007). Powers et al . (2021) assert that apprentices with excessive work throughout their apprenticeship predicted anxiety and foresaw negative interest.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Left unresolved, previous research suggests this increased stress could impact course retention (Cvetkovski et al, 2018) and the mental health of the apprentices. Furthermore, research has shown that increased anxiety and stress are not conducive to an effective work environment (Powers and Watt, 2021). Alan felt "really overwhelmed and (I) actually came home and said to my husband 'I'm going to quit'" whereas Amrit felt they were like "rabbits in the headlights as to what to expect".…”
Section: University Inductionmentioning
confidence: 99%